The Effects of Photoinitiator Addition to the Mechanical and Physical Properties of the Epoxy and Vinyl Ester Fiber Glass Laminated Composites - Ramli, Junid (Centre for Promoting Ideas, USA, 2011)

(untitled)
Ultra-violet (UV) curing process is introduced in the curing of polymer matrix composites (PMC) for the application in producing bullet proof vest. Two types of matrix materials were used: epoxy and vinyl ester. Each of them were mixed with different types of photoinitiator; Bisacyl Phosphine Oxide (BaPO) and Alpha Hydroxyl Ketone Peroxide (AHK) at 1.0 and 10.0 per hundred of resin (phr) from the total proportion of the mixture. Sandwich construction of composite was done by hand lay-up process where the mixture was wiped on the fiber layers. The laminate was then tested to determine its characteristics of physical properties and its behavior to applied loads. Morphological observation through Scanning Electron Microscope (SEM) was performed in order to evaluate the quality of adhesion between each fiber layer and matrix wetting behavior. Vinyl ester is not recommended to be used as the matrix since two days is required to make it fully cured unlike epoxy which was rapidly cured once exposed under the UV light. The physical testing shows that optimum density for the effect of photoinitiator obtained at 1.0phr for epoxy and 10.0phr for vinyl ester. This could give benefit to the manufacturer since it gives lower weight compared to virgin matrix materials. The effect of photoinitiator to the tensile strength shows optimum results at 1.0 phr for both epoxy and vinyl ester. On the other hands, effect of photoinitiator to the hardness of the composite is found optimum at the present of 1.0 phr for both matrix materials.